What is improvement science, and what makes it different? An outline of the field and its frontiers - Reed, Julie E.; Antonacci, Grazia; Armstrong, Natalie; Baker, G. Ross; Crowe, Sonya; Harenstam, Karin Pukk; Hargreaves, Dougal; Jani, Yogini H.; Provost, Lloyd; Rejler, Martin; Savage, Carl; Thor, Johan; et al. (Frontiers in Health Services, 2025)
Improvement science has emerged as an interdisciplinary field of enquiry to provide methodological and scientific rigour to the practice and study of improvements in healthcare, and with contributions from a wide range of stakeholders and perspectives. However, compared to more well-established health-related sciences, the science of improvement remains in relative infancy. Whilst the improvement community has grown considerably, there is no existing articulation of the scope of what matters to the health and social care improvement community, and how this aligns to the enquiries of the field of improvement science. This paper aims to outline key areas of interest to the improvement community, and to propose distinguishing features of improvement science that help differentiate it from other areas of enquiry. Two over-arching research questions are identified, along with ten associated areas of enquiry which are grouped into three clusters: (1) improvement in practice, (2) aligning improvement efforts and (3) advancing the contribution of the improvement community. Four features that collectively define and distinguish the field of improvement science are proposed. The outline of the improvement landscape provides a common language for the diverse improvement community, supporting people to transcend disciplinary interests and constraints, and to consider how, collectively, we can improve health and care. Others are invited to refine and advance mapping of the improvement landscape by identifying gaps and increasing contributions from diverse perspectives.